Study of the leadership styles of the public secondary school administrators and the performance of the faculty: Paranaque school division - Sombilla, Rolando S. (Parañaque City: Olivarez College, 2000)
The descriptive-correlational research approaches with the use of personal information sheet and questionnaire on leadership style of Filipino administrators were used to generate data for this study. They contained items which gave data for this study. They contained items which gave data on the following: 1. The profile and leadership styles of the public secondary school administrators. 2. The profile and performance of the faculty. The researcher utilized the personal information sheet labeled as questionnaire form A which solicited personal characteristics or profile of the respondents of the study such as age, sex, civil status, educational attainment,number of years in the service and the number of children. The researcher made use of questionnaire form B taken from the Management Styles of Selected Filipino Managers in Metro Manila. (Tobias) a dissertation wrote by Mario O. Tobias. The questionnaire served as an inventory of questions which may categorize a Filipino leadership system into one of the four and these were the Realist, the Idealist, the Opportunist and the contingent. The items of the questionnaire were taken from the definitions and characteristics of the leadership styles and were arranged according to the four leadership styles as they are arranged above. The highest score in a leadership style measured the styles of the respondents. The categorizations were based on adding all the encircled numbers which represented their answers to the degree of their leader behavior. The sums of all the encircled numbers for every ten items representing each of the Filipino leadership style was divided by ten.
Master Thesis
Keywords: Filipino leadership; Leader behavior; Quality Eduacation